SISTEM INFORMASI PENDATAAN ALAT BANTU BAGI PENYANDANG DISABILITAS PADA DINAS SOSIAL ACEH - Windy Anggara, Aprillian (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2020)
One agency that only utilizes the information system manually using Microsoft Word and Excel applications in its data collection is carried out by the Aceh Social Service, which is related to the Assistance Data Collection Information System for Persons with Disabilities which results in the process of making reports being late because they have to open many folders and files. files to collect data in accordance with the desired report from the leadership. From the description, the purpose of writing is to find out and design a Data Collection Information System for Assistive Devices for Persons with Disabilities at the Aceh Social Service using a web-based programming language. There are two methods that the authors use to collect data, namely; field studies and literature studies. Based on the results of observations and the author can draw a conclusion that includes the data collection process for disability tools using an online-based system that is easier to do because it is supported by special reporting for the assistance of disability tools and applications are built using web-based programming languages ​​such as PHP, HTML, CSS., JavaScript, and MySQL as the database.